A contribution spanning three time periods offered by artificial intelligence and synthetic biology - Sven, Diaconescu Ada; Bellman, Francesco; Nurdiyanto, Heri (Universitas Dharma Wacana, 2023)
The field of synthetic biology benefits significantly from the application of artificial intelligence. I'd want to make three suggestions, which all have something to do with the past, the present, and the future of artificial intelligence. The works of Turing and von Neumann in biology and artificial systems from the past are exciting to investigate within the new framework of synthetic biology, particularly regarding the concepts of self-modification and self-replication as well as their links to the emergence and the bottom-up approach. The ongoing epistemological investigation into the emergence and the research being conducted on swarm intelligence, superorganisms, and biologically inspired cognitive architecture may result in discoveries on the potential uses of synthetic biology to explain mental processes. Finally, the current discussion on the future of artificial intelligence and the rise of superintelligence may point to some research trends for the future of synthetic biology and help to better define the boundary of concepts such as